Electrochemical Behavior of TiO2 Nanotube/Ti Prepared by Anodizing for Micro-Lithium Ion Batteries - 박수길; 양정진; 노진우; 김홍일; HirokiHabazaki (전기화학회지, 17(1), 2014)
The TiO2 nanotube/Ti electrode are used as an anode in thin-film lithium microbatteriesis known to have high oxidation-reduction potential of 1.8 V (vs. Li/Li+). It can preventfrom dendrite growth of lithium during charging. The TiO2 nanotube/Ti electrode was preparedby anodizing at constant voltages for thin-film lithium microbatteries. The capacities of TiO2nanotube/Ti anode prepared by anodizing at 10 V, 20 V and 30 V were observed to be23.9 μAh cm−2, 43.1 μAh cm−2 and 74.0 μAh cm−2. We identified it was found that the capacityof TiO2 nanotube/Ti increases with increasing anodizing voltage and the anatase structure ofTiO2 nanotube/Ti compared with amorphous structure has batter cycle performance than amorphousTiO2 nanotube/Ti. KCI Citation Count: 0